2016
DOI: 10.4238/gmr.15026963
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects and mechanisms of Ndfipl on SH-SY5Y cell apoptosis in an in vitro Parkinson’s disease model

Abstract: ABSTRACT. The aim of the current study was to examine the protective effects and mechanisms of Ndfipl on neurocytes in an experimental in vitro Parkinson's disease model induced by MPP We further studied the roles of Ndfipl in inhibiting MPP + -induced SH-SY5Y apoptosis, protection, and ubiquitination of SH-SY5Y cells. Our results showed that Ndfipl reduced apoptosis and improved cell survival rate, indicating that Ndfipl has a neuroprotective effect. Furthermore, we found that Ndfipl binds to Nedd4-1, and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Accompanied by an increased level of Ndfip1, the protein levels of both DMT1-IRE and DMT1-nonIRE are decreased dramatically. Our results are consistent with previous studies in PD models, Ndfip1 is decreased in 6-OHDA-treated rats and MES23.5 cells, whereas Ndfip1 overexpression leads to a decrease in DMT1 level in vitro (Howitt et al, 2014 ; Jia et al, 2015 ; Liu et al, 2015 ; Xing et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Accompanied by an increased level of Ndfip1, the protein levels of both DMT1-IRE and DMT1-nonIRE are decreased dramatically. Our results are consistent with previous studies in PD models, Ndfip1 is decreased in 6-OHDA-treated rats and MES23.5 cells, whereas Ndfip1 overexpression leads to a decrease in DMT1 level in vitro (Howitt et al, 2014 ; Jia et al, 2015 ; Liu et al, 2015 ; Xing et al, 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…Data are mean ± SEM of at least three independent experimental runs, with samples collected from multiple passages of cells. * P < .05; * * P < .01. role in neuronal development [18 , 19] and its importance in neurodegeneration has been increasingly documented in the literature [20][21][22][23][24][25] . Our findings showed that Nedd4-1 increased in both human AD patient and J20 mouse (age-dependently) hippocampus, which is similar to previous findings in neurodegenerative conditions [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Both Nedd4-1 and Nedd4-2 are involved in the ubiquitination of several mammalian transporters in various cellular systems [12][13][14][15][16][17] . Further, Nedd4-1 plays a crucial role in neuronal development [18 , 19] and its importance in neurodegeneration has been recognized in recent years [20][21][22][23][24][25] . A classical Nedd4 protein interacting motif ("PPXY") allows specified association with protein substrates [14 , 26] .…”
Section: Introductionmentioning
confidence: 99%
“…NEDD4-1 also interacts with NDFIP1 (NEDD4 family interacting protein), a trans-membrane protein with a protective role in a cell model of PD, helping reduce apoptosis and improving cell survival rate. This binding generates enhanced expression of NDFIP1 [ 108 ]. Loss of NEDD4-1 has been associated with elevation of RTP801, a pro-apoptotic protein sufficient and necessary to induce neuronal death in cellular and animal models of PD [ 109 ].…”
Section: Nedd4 E3 Ligases In Neurodegenerationmentioning
confidence: 99%